Bosch in detail - Borchert, Till-Holger (Ludion, 2016)
Hieronymus Bosch is one of the most famous painters in the history of Netherlandish painting, if not the world. This new book presents his best-known works, revealing them as never before in magnificent, full-page close-up details. Chapters explore characteristic themes in Bosch's work, such as faces, visions of heaven and hell, the four elements, landscapes, and creatures both fantastic and monstrous. 'Bosch in detail' offers an exceptional insight into masterpieces like 'The garden of earthly delights', 'The Haywain', the 'Temptation of St Anthony and the last judgment'. Author Till-Holger Borchert, an expert in Netherlandish art, guides us through this popular painter's work in clear and accessible language, and from less-familiar and even surprising angles